PHARMACOLOGICAL EVALUATION FOR ANTIDEPRESSANT ACTIVITY OF VANDA SPATHULATA IN MICE - RAJANEEKAR DASARI,; D. SATHYAVATHI,; SAMPATH KUMAR BELIDE,; B.R.SOUMYA, (International Journal of Pharma and Bio Sciences, 2013)
The present study was designed to screen the antidepressant potential of Vanda spathulata using forced swim test and tail suspension test. Imipramine (30mg/kg) and Fluoxetine (20mg/kg) were used as standard drugs. The vehicle (10ml/kg, p.o), fluoxetine (20mg/kg, i.p.), imipramine (30mg/kg, i.p.) and Vanda spathulata (100mg/kg, 200mg/kg and 400mg/kg, p.o. respectively) were administered for 14 days. Duration of immobility was noted in both the models. In our study, both imipramine and Vanda spathulata significantly reduced the duration of immobility was obseved when compared to control group. The antidepressant activity of Vanda spathulata was comparable to that of standard drug impramine. Significant decrease in brain MAO-A and MAO-B activities levels were observed upon methanolic extract administration to mice as compared to control. Therefore, methanolic extract of Vanda spathulata showed significant antidepressant activity probably by inhibiting MAO-A and MAO-B. Hence, methanolic extract of Vanda spathulata may be explored further for the management of mental depression.